EXPLORING THE USE OF TEACHER'S CODE-SWITCHING IN THE CONTEXT OF TEACHING ENGLISH IN SENIOR HIGH SCHOOL - Musazsa, Nisa'u Qurrota A'yun; Andayani T, Made Adi; Bilqis, Mutiara (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
This study explored the use of teachers’ code-switching in the context of Indonesian EFL classrooms. This study was a descriptive case study research, conducted at one of the state senior high schools in Jember, Indonesia, involving one English teacher who taught four different classes. The data were collected by observing and recording the teaching-learning classrooms and conducting an interview with the English teacher. The recordings were transcribed and analyzed using the content analysis method proposed by Krippendorff (2004) to identify and describe the types and functions of code-switching used by the English teacher. The findings revealed that the three types of code-switching, namely inter-sentential switching, intra-sentential switching, and tag-switching, as defined by Poplack (1980), occurred during the teaching-learning process. It showed that Inter-sentential switching was the most frequently used type by the teacher. In addition, this study classified the teacher’s code-switching into seven functions proposed by Hoffmann (1991). The most used function was “Intention of clarifying the speech content for interlocutors” with a total number of 159 data, and the least used function was “Quoting somebody else” with a total number of 7 data. The results of the interview showed that the teacher’s code-switching occurs to meet students’ needs and may be helpful in teaching English classrooms, particularly in public schools in which students have different level of English proficiency.